ANALISIS KANDUNGAN MINERAL BERPOTENSI TINGGI PADA PASIR GALIAN DI WILAYAH KABUPATEN BANYUMAS - Zaroh Irayani; Bilalodin Bilalodin (Universitas Jenderal Soedirman, 2007)
It have been done analysis high potential mineral contents of sands and sandstone in Banyumas region. Sands and sandstone are taken from mining traditional at rivers and river’s stone grinder place. Sand samples were taken from Tajum, Logawa, Serayu and Klawing river, while sandstone were taken from Banjaran, Logawa and Klawing river’s grinder place. Sand was separate using permanent magnet to disassociated the magnetic and non magnetic mineral content and analyzed by X-ray difraction to reveal the mineral types. The Result indicated that river sand contained 39% magnetic mineral and 61% non magnetic. While identification using X-ray difraction obtained that sand have mineral of complex structured of valuable element such as Fe, Ti, Si and Zn and also rare earth like Y, Ca, Li and La.